ANALIZA STYLU INWESTOWANIA POLSKICH FUNDUSZY INWESTYCYJNYCH - Białous, Krzysztof (Wydział Prawa i Administracji UAM, 2009)
The paper presents theoretical aspects of an analysis of investment styles adopted by mutual funds, methods of their identification, and results of the research recently conducted on foreign markets and supported by an empirical analysis of investment funds active on the Polish market between July 2004 and June 2009. The main objective of the study was to determine whether funds continued to realise a policy they had originally declared. The findings were to indirectly establish whether the funds available to Polish investors have been properly classified. The recent financial crisis has also prompted the authors to attempt to answer the question whether the current crisis has had any impact on the decision making process in mutual funds and whether it has influenced their decisions of where and how to invest.
ANALYSIS OF INVESTMENT STYLES OF POLISH MUTUAL FUNDS